Workplace Spirituality and Employee Performance: Mediating Role of Organizational Citizenship Behavior and Moderating Role of Emotional Intelligence in Nepalese Construction Sector - Bhandari, Samikshya (KIC International Journal of Social Science and Management, 2024)
This study is designed to explore and determine Performance within Construction sector of Kathmandu, Nepal by shading lights on mediating and mediating role of organizational citizenship behavior and emotional intelligence respectively After analyzing the responses of the 384 respondents selected conveniently from ten oldest construction companies in Kathmandu Valley, with the application of correlation, regression, this study showed a significantly positive relationship between the constructs Workplace Spirituality, Employee Performance, and Organizational Citizenship Behavior, but there was no meaningful mediating role of on by Organizational Citizenship Behavior. However, Emotional Intelligence strengthens the link between Workplace Spirituality and Employee Performance, emphasizing the need of the emotional alignment. Likewise, the study identified challenges faced by Nepali Construction firms in intergrading WS practices and provided practical recommendations. The study suggests creating spiritual work settings, encouraging mindfulness and compassion, and providing Emotional Intelligence training hence to improve leadership, engagement, and overall growth for organizational success.